2022
DOI: 10.1038/s41598-022-23648-1
|View full text |Cite
|
Sign up to set email alerts
|

An isolated population reveals greater genetic structuring of the Australian dingo

Abstract: The Australian dingo is a recent anthropogenic addition to the Australian fauna, which spread rapidly across the continent and has since widely interbred with modern dogs. Genetic studies of dingoes have given rise to speculation about their entry to the continent and subsequent biogeographic effects, but few studies of their contemporary population structure have been conducted. Here we investigated the dingo ancestry and population structure of free-living dogs in western Victoria and contrasted it with a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We observed elevated homozygosity levels (median F het > 0.7) in the Big Desert compared to other dingo populations, suggesting the population is experiencing inbreeding (Figure 5). A recent microsatellite‐based study found the Big Desert dingo population to have genetic diversity levels up to 50% lower than other dingo populations (Stephens et al, 2022). While the absolute value of homozygosity measures calculated for dingoes in this study could be inflated due to ascertainment bias, whole genome data from a small number of captive and wild dingoes also reveal elevated homozygosity levels relative to domestic dogs (Field et al, 2022; Kumar et al, 2023; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We observed elevated homozygosity levels (median F het > 0.7) in the Big Desert compared to other dingo populations, suggesting the population is experiencing inbreeding (Figure 5). A recent microsatellite‐based study found the Big Desert dingo population to have genetic diversity levels up to 50% lower than other dingo populations (Stephens et al, 2022). While the absolute value of homozygosity measures calculated for dingoes in this study could be inflated due to ascertainment bias, whole genome data from a small number of captive and wild dingoes also reveal elevated homozygosity levels relative to domestic dogs (Field et al, 2022; Kumar et al, 2023; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, populations of dingoes with documented isolation and decreased genetic diversity, such as those on K’gari/Fraser Island (Conroy et al . 2021) and in western Victoria (Stephens et al . 2022), currently persist without noticeable negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although fragmenting populations can sometimes spur conservation concerns associated with low genetic diversity (Blanchet et al 2010), we believe this is unlikely to be a concern for dingoes in this instance; their large movement capabilities and rapid expansion across the continent since their relatively recent introduction from a small founder population indicates persistence and adaptability, despite relatively low genetic variation (Wilton et al 1999;Zhang et al 2020). In addition, populations of dingoes with documented isolation and decreased genetic diversity, such as those on K'gari/Fraser Island (Conroy et al 2021) and in western Victoria (Stephens et al 2022), currently persist without noticeable negative effects.…”
Section: Movement Barriers and Corridorsmentioning
confidence: 99%
“…In accordance with animal ethics approval, morphological data were collected and a biopsy was collected from the ear with an Allflex sampling kit ® and analysed by an independent laboratory Zoological Genetics (South Australia) by using microsatellites (Wilton 2001;Stephens et al 2015). DNA analysis was undertaken to assess kin and subpopulation relationships within the population and elsewhere across Australia, so as to gain understanding of family relationships and lineage (Stephens et al 2022). A small, coloured ear tag was fitted into the biopsy hole to aid identification at a distance and a microchip was inserted into the nape.…”
Section: Handling and Collaringmentioning
confidence: 99%